An Experimental Investigation of Self-Serving Biases in an Auditing Trust Game: The Effect of Group Affiliation - King, Ronald R. (The Accounting Review, 2002)
I report the results of an experiment designed to investigate the influence of noncredible communications and group affiliation on auditors' formation of self-serving bias. I find that manager-subjects use noncredible communications to induce auditors to develop an unwarranted trust of managers (i.e., a biased judgment). However, the bias is neutralized when auditor-subjects belong to groups that create social pressure to conform to group norms. Thus, my finding calls into question the Bazerman et al. (1997) conclusion that auditors cannot conduct impartial audits due to self-serving biases resulting from repeated interactions between auditors and their clients.